Bats of Florida - Holly K. Ober; Martin B. Main; Ginger M. Allen (EDIS)
Nocturnal habits, affinity for eerie places, and silent, darting flight have made bats the subjects of a great deal of folklore and superstition through the years. Given their ability to function in the dark when and where humans cannot, it is no wonder that bats have long been associated with the supernatural. Bats remain poorly understood even today. This revised 5-page fact sheet describes the species of bats that occur in Florida and provides simple tips for their identification. It was written by Holly K. Ober, Martin B. Main, and Ginger M. Allen and published by the UF Department of Wildlife Ecology and Conservation, November 2010.